ASSOCIATED RISK FACTORS AND PREVALENCE OF METABOLIC SYNDROME IN PEOPLE WHO ARE LIVING WITH HIV AND ARE ON ANTIRETYROVIRAL TREATMENT - Petreska, Biljana Jovan; Stevanovic, Milena; Topuzovska, Irena Kondova; Saveski, Velimir; Arsik, Elena (Journal of Morphological Sciences, 2025)
The extended life expectancy of people living with HIV infection increases the risk of metabolic syndrome (MS). To assess the prevalence of MS, the association of triple regimen antiretroviral therapy (ART) and the role of the chronic inflammatory process caused by the HIV virus with the onset of MS. A prospective cross-sectional study was conducted on 141 HIV infected adult patients with confirmed HIV infection who regularly receive ART at the University Clinic for infectious diseases and febrile conditions in Skopje. In all patients, the presence of MS was determined according to the criteria of the National Cholesterol Education Program Adult Treatment Panel ATP III (NCEP ATPIII) 2005. The statistical software SPSS (ver. 23.0; IBM, SPSS, USA) was used for statistical analysis.   The prevalence of MS in persons with HIV infection in RNM was 17.96%. The group of patients with MS were significantly older and had significantly higher Body Mass Index and greater waist circumference (28.82 ± 4.6 kg/m 2 vs 23.91 ± 3.6 kg/m 2   p<0.0001) and (101.04 ± 12.4 vs 87.19 ± 9.8cm,p<0.0001), respectively. Treatment of patients with ART did not show a significant difference in the group with and without MS. There is a significant difference regarding the frequency of IL 6 (p=0.012). Aging and increasing Body Mass Index are significant risk factors in the developing of MS in persons with HIV infection who are on ART treatment. Key words:  metabolic syndrome, HIV infection, antiretroviral treatment.